A highly pathogenic avian influenza virus H5N1 clade 2.3.4.4 detected in Samara Oblast, Russian Federation - Glazunova, Anastasia; Krasnova, Elena; Bespalova, Tatiana; Sevskikh, Timofey; Lunina, Daria; Titov, Ilya; Sindryakova, Irina; Blokhin, Andrey (Frontiers in Veterinary Science, 2024)
Avian influenza (AI) is a global problem impacting birds and mammals, causing economic losses in commercial poultry farms and backyard settings. In 2022, over 8,500 AI cases were reported worldwide, with the H5 subtype being responsible for many outbreaks in wild and domestic birds. In the territory of the Russian Federation, outbreaks of AI have been massively reported since 2020, both among domestic bird species and wild bird species. Wild migratory birds often serve as natural reservoirs for AI viruses, and interactions between bird species can lead to the emergence of new, highly pathogenic variants through genetic recombination between strains.In order to combat the widespread outbreaks of the disease and potential risks of further spread in 2021, monitoring studies were conducted in the Samara region, the southeastern region of European Russian Federation. These studies aimed to diagnose and characterize circulating AI virus variants among wild migratory birds during waterfowl hunting in areas of mass nesting. Among the 98 shot birds, a highly pathogenic A/H5N1 AI virus was detected in a Eurasian Teal from the Bolshechernigovsky district. It was classified into clade 2.3.4.4 based on the cleavage site structure of HA. Phylogenetic analysis showed a high relatedness of the identified strain in the Samara Oblast with field isolates from Russia, Nigeria, Bangladesh, and Benin.The article emphasizes the importance of monitoring AI virus spread in both wild and poultry, highlighting the need for timely information exchange to assess risks. Further comprehensive studies are necessary to understand virus dissemination pathways.